Experiences of Students in Recovery on a Rural College Campus: Social Identity and Stigma. (November 2016) - Scott, Alison; Anderson, Ashton; Harper, Kristen; Alfonso, Moya L.
A growing number of college (postsecondary) students are in recovery from addiction to drugs or alcohol. In this article, we discuss the experiences of students returning to a university campus after long-term addiction treatment. We also explore the role of a Collegiate Recovery Program (CRP) in providing support, and in helping the students develop post-addiction identities that will sustain them. To do so, we draw on Goffman's ideas related to stigma, as well as conceptualizations of identity reconstruction as a practiced, lived experience. Students interviewed faced a double bind; they sought to escape the stigmatized identity of "addict, " but could not identify as typical students because of their abstinence from alcohol and drugs. The CRP helped them manage the transition to student life, provided a safe haven on campus, and provided an alternate and positive identity: a student in recovery.